-2v+43=3(v+1)

Simple and best practice solution for -2v+43=3(v+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2v+43=3(v+1) equation:



-2v+43=3(v+1)
We move all terms to the left:
-2v+43-(3(v+1))=0
We calculate terms in parentheses: -(3(v+1)), so:
3(v+1)
We multiply parentheses
3v+3
Back to the equation:
-(3v+3)
We get rid of parentheses
-2v-3v-3+43=0
We add all the numbers together, and all the variables
-5v+40=0
We move all terms containing v to the left, all other terms to the right
-5v=-40
v=-40/-5
v=+8

See similar equations:

| X*4x=40 | | -100-4x-2x2=0 | | n+(n+.6)=2n+(n+.1) | | 65=10x-45 | | n+(n+.6)=n+(n+.1) | | 2n+2(2n+.6)=4n+2(n+.1) | | 2(2n+.06)=2(3n+.1) | | 5x/3+14=9 | | 31+x+90/4=90 | | 10h-29=59 | | 5x^2+9=134 | | 84=3x=90 | | A=9/8(h-21) | | P2=4p+96 | | 5x^2-9=134 | | 42=1/2(7)h | | 2(x+9)−2=79−5x | | 55+2/x=90 | | 55+2x=90 | | 12/8=7.5/x | | (-14)+5/6v=1 | | 24+6x=90 | | 128=7.5x4 | | 24+6x=50 | | -3x-3(x-15)=-15 | | 3x³+6x²+45x=0 | | 5n+7=20 | | 3x^3+6x^2+45x=0 | | 2(2x)=10=3x=13 | | x-14)/(-4=3) | | X3-x=449 | | -2x-3(x-6)=-12 |

Equations solver categories